Meal Replacements in the Treatment of Adolescent Obesity: A Randomized Controlled Trial - Berkowitz, Robert I. (2010)
The use of meal replacements (MR) in lifestyle modification programs (LMP) for obese adults significantly increases weight loss, compared with the prescription of an isocaloric conventional diet (CD). The present 12-month randomized trial examined 113 obese adolescents (mean [SD] age of 15.0 [1.3] yr and body mass index [BMI] of 37.1 [5.1] kg/m(2)) who were assigned to a LMP, combined with CD or MR (randomized in 1:2 ratio). For months 1–4, all participants were prescribed 1,300–1500 kcal/d, consumed as a CD or as 3 Slim-Fast® shakes/d and one pre-packaged meal/d (with 5 fruit/vegetable servings/d). After month 4, participants were unmasked to their random assignment of continued use of MR (i.e., MR+MR) or transitioned to CD (i.e., MR+CD). Those initially treated by CD continued with it (i.e., CD). Regression models were used to evaluate percentage change in BMI from baseline to month 4, months 5 to 12, and baseline to month 12. At month 4, participants assigned to MR (N=65) achieved a mean (+SE) 6.3±0.6% reduction in BMI, compared to a significantly (P=0.01) smaller 3.8±0.8% for CD participants (N = 37). From months 5–12, BMI increased significantly (P<0.001) in all three treatment conditions (i.e., MR+MR, MR+CD, and CD), resulting in no significant (P=0.39) differences between groups in percentage change in BMI at month 12. Across groups, mean reduction in BMI from baseline to month 12 was 3.4±0.7% (p<0.01). Use of MR significantly improved short-term weight loss, compared with CD, but its continued use did not improve the maintenance of lost weight.